A New Approach to Rebates After Intel Case - Fišer Šobot Sandra (LeXonomica, 2018)
Although heated debates are quite common in the law on abuses of dominant position, it is not an exaggeration to state that Intel case has generated an unusual storm of comments and discussions. In 2009, the European Commission fined Intel 1.06 billion € for abusing dominant position by granting exclusivity rebates. In 2014, the General Court rendered judgment in support of the European Commission`s decision. In 2017, the Court of Justice of the European Union set aside that judgment and referred the case back to the General Court in order for it to examine Intel`s arguments regarding the capacity of the rebates at issue to restrict competition. This long awaited ruling in the Intel case is so far one of the most important judgments regarding exclusivity rebates and Art. 102 TFEU enforcement. The paper addresses relevant issues and conclusions in relation to the exclusivity rebates. Additionally, the author attempts to assess possible effects and implications of the Courts of Justice`s judgment. Pristop do rabatov po zadevi Intel Čeprav so na področju zlorab prevladujočega položaja vroče razprave nekaj običajnega, je vendarle primer Intel povzročil neobičajen plaz komentarjev in razprav. V letu 2009 je Komisija EU kaznovala podjetje Intel z 1,06 milijarde evrov zaradi zlorabe prevladujočega položaja z dodeljevanjem ekskluzivnih rabatov. To odločitev Komisije EU je Splošno sodišča v letu 2014 potrdilo. V letu 2017 pa je Sodišče EU odločbo razveljavilo in zadevo vrnilo Splošnemu sodišča, da preuči argumente podjetja Intel v zvezi z omejevanjem konkurence. Ta dolgo pričakovana odločba Sodišča EU je do sedaj ena najpomembnejših odločb, ki obravnava ekskluzivne rabate v okviru 102. člena PDEU. V zvezi s tem prispevek obravnava relevantna vprašanja in podaja zaključke, prav tako pa avtorica skuša oceniti verjetne učinke in vpliv te odločbe Sodišča EU.